2011
DOI: 10.3109/09638288.2011.635746
|View full text |Cite
|
Sign up to set email alerts
|

Pacing as a strategy to improve energy management in myalgic encephalomyelitis/chronic fatigue syndrome: a consensus document

Abstract: Pacing offers practitioners an additional therapeutic option which is acceptable to the majority of patients and can reduce the severity of the exertion-related symptoms of ME/CFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
96
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 73 publications
(144 reference statements)
1
96
1
4
Order By: Relevance
“…The most commonly experienced symptoms are fatigue, pain, and cognitive problems (Anderson, Jason, Hlavaty, Porter, & Cudia, 2012;Goudsmit, Nijs, Jason, & Wallman, 2012). People with CFS may experience restricted performance in a variety of life domains, including employment, education, personal care, home care, leisure, and social relationships, although their symptoms are not always visible to others in their environment (Anderson et al, 2012;Taylor et al, 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly experienced symptoms are fatigue, pain, and cognitive problems (Anderson, Jason, Hlavaty, Porter, & Cudia, 2012;Goudsmit, Nijs, Jason, & Wallman, 2012). People with CFS may experience restricted performance in a variety of life domains, including employment, education, personal care, home care, leisure, and social relationships, although their symptoms are not always visible to others in their environment (Anderson et al, 2012;Taylor et al, 2010).…”
mentioning
confidence: 99%
“…The rationale for activity pacing can be found in several strategies observed in people with CFS: reduced activity levels resulting from and in anticipation of fatigue (Nijs et al, 2011;Vercoulen et al, 1997), lowered activity peaks followed by very long rest periods (van der Werf, Prins, Vercoulen, van der Meer, & Bleijenberg, 2000), and ability to perform short periods of light to moderate activity without exacerbating symptoms (Clapp et al, 1999;Cook et al, 2005). Several randomized controlled trials (RCTs) have shown positive effects of treatment programs based on activity pacing for people with CFS (Cox, 2002;Crawley et al, 2013;Goudsmit et al, 2012;Jason et al, 2013;Pemberton & Cox, 2014;Taylor, 2004). The findings of these studies are in line with those of a pilot study in which several of the current authors participated (Nijs et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Målsetningen er at man aldri skal overskride den individuelle tålegrensen (91) . Pacing hjelper pasienter med CFS/ME å begrense anstrengelsesutløste symptomforverringer og er derfor godt egnet for pasienter som holder seg på eller naer sitt maksimale funksjonsnivå (94) .…”
Section: Aktivitets Og Energireguleringunclassified
“…Både EET og pacing retter seg mer direkte inn mot forebygging av anstrengelsesutløste symptomer og ser ut til å kunne bidra til stabilisering av sykdommen, økt funksjon og forebygging av symptomforverringer (94)(95)(96) . Begge tilnaermingene vil kunne egne seg som del av et individualisert, tverrfaglig mestringsopplegg-eller et rehabiliteringsprogram.…”
Section: Aktivitets Og Energireguleringunclassified